Root Growth Stimulation In Rice (Oryza Sativa L.) By Seed Bio Priming With Trichoderma Sp. (Applied Biological Research, 2016)
Trichoderma species are commonly used as biological control agents  against phytopathogenic fungi and some of its strains are able to  produce metabolites that enhance plant growth. In current study the  elite rice germplasm population was used for the assessment of root  pulling strength (RPS). RSP showed positive correlation with root length  and other root parameters. On the basis of RSP, 10 lines each with  higher root pulling strength (HRPS) and minimum root pulling strength (MRPS) were selected to check the effect of different Trichoderma spp.  on root traits by seed biopriming. RPS varied from 21.5 for rice  genotype ‘SLO-16’ to 40 for ‘Cross 116’ and ‘Bhata Phool’. Greater RPS  reflected dense root system or greater root length/volume. This analysis  revealed that the response of Trichoderma spp. varied with different rice  cultivars. Roots were analyzed using Epson perfection v700/v750 3.81  version scanner with WinRhizoReg software. All the isolates of IRRI  showed positive response on increase in root length. The growth was enhanced in presence of rhizosphere-competent endophytic strains of  Trichoderma, and these characteristics were strain-specific and not  characteristic for species. These endophytic plant symbionts can be  widely used as seed treatment to control diseases and enhance plant  growth and yield.
Keywords: Plant growth promoting response (PGPR); rice; root pulling strength; root scanning; Trichoderma